2008
DOI: 10.1007/s00268-007-9424-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Posture and Prolonged Pneumoperitoneum on Hemodynamic Parameters during Laparoscopy

Abstract: Patients undergoing totally endoscopic radical prostatectomy with 4 h of pneumoperitoneum in the Trendelenburg position experienced no significant hemodynamic depression during posture and pneumoperitoneum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
1
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 27 publications
2
36
1
7
Order By: Relevance
“…This must be balanced against the cardiovascular and respiratory effects that this position may cause particularly when combined with a pneumoperitoneum. Lee et al 20 reported a reduction in cardiac index by as much as 50% following head down tilt; however, Meininger et al 21 reported that this results in minimal haemodynamic depression during the first 4 h of RARP. Thoracic emphysema, cerebral irritation and laryngeal oedema, presenting as postextubation respiratory distress, have all been reported.…”
Section: Patient Positioningmentioning
confidence: 99%
“…This must be balanced against the cardiovascular and respiratory effects that this position may cause particularly when combined with a pneumoperitoneum. Lee et al 20 reported a reduction in cardiac index by as much as 50% following head down tilt; however, Meininger et al 21 reported that this results in minimal haemodynamic depression during the first 4 h of RARP. Thoracic emphysema, cerebral irritation and laryngeal oedema, presenting as postextubation respiratory distress, have all been reported.…”
Section: Patient Positioningmentioning
confidence: 99%
“…Komplexe Eingriffe mit extremen Lagerungen und möglicherweise entsprechenden kardiopulmonalen Auswirkungen erfordern auf beiden Seiten eine Spezialisierung und Erfahrung mit dem durchzuführenden Eingriff. Dies erlaubt bei gängigen Lagerungen eine sichere Narkose ohne unbeherrschbare Auswirkungen auf die Hämodynamik und Beatmungsfähigkeit [32].…”
Section: Lagerungsbedingte Schwierigkeiten Und Spezielle Aspekte Der unclassified
“…Estas alterações resultam em hipóxia e/ou hipercarbia. 7,8,9 A perfusão tecidual inadequada leva à acidose metabólica, que pode ser detectada através de gasometria ou através de elevação dos níveis séricos de lactato. Esta situação é potencialmente deletéria, pois promove diminuição da contratilidade cardíaca, do índice cardíaco e da responsividade vascular periférica, além de proporcionar aparecimento de arritmias ventriculares ou dificultar o controle de arritmias já existentes.…”
Section: Introductionunclassified